Baccharis salicifolia aqueous extracts as antihelmintic treatment - María P. Saracino; Esteban Chaves; Cecilia C. Vila; Cecilia B. Dobrecky; Tomás Lombardo; Mariángeles Díaz; Rafael A. Ricco; Pablo C. Baldi; Ignacio J. Agudelo (Advances in Traditional Medicine, 2026)

Upper respiratory microbiome composition and associations with air pollution and infant respiratory health: a longitudinal study in Guatemala - Rina Das; Andrew Baldi; Sant-Rayn Pasricha; Lisa M. Thompson; Anaité Díaz-Artiga; Laura Maria Grajeda; John P. McCracken; Kelsey Jesser; Lance Waller; Matthew C. Freeman; Thomas Clasen; Sheela S. Sinharoy (International Journal of Hygiene and Environmental Health, 2026)

Genetic correlations between carcass traits measured by ultrasonography and semen quality traits in Nellore cattle incorporating genomic information - Camila S. Mussi; Gabriel C. Medeiros; Rafael Espigolan; Fernando Baldi; Marcio R. Silva; José D. Guimarães; Elisangela C. Matos; Joanir P. Eler; Tamires Miranda Neto; José Bento S. Ferraz; Luiz F. Brito (Livestock Science, 2025)

A holo-omics analysis shows how sugar kelp can boost gut health in Atlantic salmon - Jacob A. Rasmussen; Annette Bernhard; Laurène A. Lecaudey; Varsha Kale; Germana Baldi; Lene S. Myrmel; Martin Hansen; Jaelle C. Brealey; Sarah S.T. Mak; Ida B. Nielsen; Lorna Richardson; Lise Madsen; et al. (Aquaculture, 2025)

Climate change impacts on the potential global distribution of Maconellicoccus hirsutus - Iro A. Georgopoulou; Dimitrios P. Papachristos; Panagiotis G. Milonas; Sonia Alkafy Baldi; Darren J. Kriticos (Biological Invasions, 2025)

Effect of long-term compost fertilization on the distribution of organic carbon and nitrogen in soil aggregates - P. Gioacchini; E. Baldi; D. Montecchio; M. Mazzon; M. Quartieri; M. Toselli; C. Marzadori (CATENA, 2024)

Pesticide exposure in greenspaces: Comparing field measurement of dermal contamination with values predicted by registration models - L. de Graaf; M. Bresson; M. Boulanger; M. Bureau; Y. Lecluse; P. Lebailly; I. Baldi (Science of The Total Environment, 2024)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Stealth invasions on the rise: rapid long-distance establishment of exotic pines in mountain grasslands of Argentina - Tomás Milani; Esteban G. Jobbágy; Martín A. Nuñez; M. Eugenia Ferrero; Germán Baldi; François P. Teste (Biological Invasions, 2020)

Matrix detachment and proteasomal inhibitors diminish Sulf-2 expression in breast cancer cell lines and mouse xenografts - Ashwani Khurana; Deok Jung-Beom; Xiaoping He; Sung-Hoon Kim; Robert C. Busby; Laura Lorenzon; Massimo Villa; Alfonso Baldi; Julian Molina; Matthew P. Goetz; Viji Shridhar (Clinical & Experimental Metastasis, 2013)

The morphological evolution of the Sciara del Fuoco since 1868: reconstructing the effusive activity at Stromboli volcano - Maria Marsella; P. Baldi; M. Coltelli; M. Fabris (Bulletin of Volcanology, 2012)

A survey of dioxins (PCDDs and PCDFs) and dioxin-like PCBs in sheep and goat milk from Campania, Italy - M. Esposito; F.P. Serpe; S. Cavallo; R. Pellicanò; P. Gallo; G. Colarusso; R. D’ambrosio; L. Baldi; G. Iovane; L. Serpe (Food Additives & Contaminants Part B-Surveillance, 2010)

Rock weathering creates oases of life in a High Arctic desert - Sara Borin; Stefano Ventura; Fulvia Tambone; Francesca Mapelli; Florence Schubotz; Lorenzo Brusetti; Barbara Scaglia; Luigi P. D'Acqui; Bjørn Solheim; Silvia Turicchia; Ramona Marasco; Kai‐Uwe Hinrichs; et al. (Environmental Microbiology, 2010)
Summary During primary colonization of rock substrates by plants, mineral weathering is strongly accelerated under plant roots, but little is known on how it affects soil ecosystem development before plant establishment. Here we show that rock mineral weathering mediated by chemolithoautotrophic bacteria is associated to plant community formation in sites recently released by permanent glacier ice cover in the Midtre Lovénbreen glacier moraine (78°53′N), Svalbard. Increased soil fertility fosters growth of prokaryotes and plants at the boundary between sites of intense bacterial mediated chemolithotrophic iron‐sulfur oxidation and pH decrease, and the common moraine substrate where carbon and nitrogen are fixed by cyanobacteria. Microbial iron oxidizing activity determines acidity and corresponding fertility gradients, where water retention, cation exchange capacity and nutrient availability are increased. This fertilization is enabled by abundant mineral nutrients and reduced forms of iron and sulfur in pyrite minerals within a conglomerate type of moraine rock. Such an interaction between microorganisms and moraine minerals determines a peculiar, not yet described model for soil genesis and plant ecosystem formation with potential past and present analogues in other harsh environments with similar geochemical settings.

High precision photogrammetry for monitoring the evolution of the NW flank of Stromboli volcano during and after the 2002–2003 eruption - P. Baldi; M. Coltelli; M. Fabris; M. Marsella; P. Tommasi (Bulletin of Volcanology, 2008)

Influence of the sample collection method on salivary interleukin–6 levels in resting and post-exercise conditions - M. A. Minetto; M. Gazzoni; F. Lanfranco; M. Baldi; L. Saba; R. Pedrola; P. V. Komi; A. Rainoldi (European Journal of Applied Physiology, 2007)

Heterologous Expression of Biologically Active Porcine Lactoferrin in Pichia Pastoris Yeast - C. Pecorini; F. Savazzini; P. A. Martino; E. Fusi; C. Fogher; A. Baldi (Veterinary Research Communications, 2005)

Cloning and linkage mapping of resistance gene homologues in apple - P. Baldi; A. Patocchi; E. Zini; C. Toller; R. Velasco; M. Komjanc (Theoretical and Applied Genetics, 2004)

Monte Carlo Inversion of DInSAR Data for Dislocation Modeling: Application to the 1997 Umbria-Marche Seismic Sequence (Central Italy) - S. Stramondo; S. Santini; P. Baldi; M. Dragoni; A. Piombo; S. Salvi; G. Spada (Pure and Applied Geophysics, 2004)

Clinical and Diagnostic Aspects of Relapsing Meningoencephalitis due to Brucella suis - Wallach J.; Baldi P.; Fossati C. (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

Modeling coseismic displacements resulting from SAR interferometry and GPS measurements during the 1997 Umbria-Marche seismic sequence - S. Salvi; S. Stramondo; M. Cocco; M. Tesauro; I. Hunstad; M. Anzidei; P. Briole; P. Baldi; E. Sansosti; G. Fornaro; R. Lanari; F. Doumaz; et al. (Journal of Seismology, 2000)

How sensory maps could enhance resolution through ordered arrangements of broadly tuned receivers - P. Baldi; W. Heiligenberg (Biological Cybernetics, 1988)